Validation of the German version of the pregnancy-related anxiety scale (PrAS): psychometric properties across all trimesters of pregnancy - Tobias Weigl; Robyn Brunton; Rachel Dryer; Susan Garthus-Niegel (BMC, 2023)
Abstract Background Pregnancy-related anxiety has received greater research attention recently given its association with adverse outcomes (e.g., negative birth experiences). The Pregnancy-related Anxiety Scale (PrAS) offers the possibility to assess pregnancy-related anxiety, but no German version is available. Therefore, the aim of this study was to validate a German version of the PrAS, a comprehensive measure with eight dimensions. Methods Pregnant women of any parity or gestation completed an online survey consisting of the PrAS, PRAQ-R2, and measures of anxiety, depression, and resilience. The PrAS was translated into German (PrAS-G) using the back-translation method. Data were subjected to confirmatory factor analysis and inferential statistics. Results Complete data were provided by 443 women. Participants were predominantly German nationals, partnered, and well-educated with a planned pregnancy. Approximately half were nulliparous. The eight-factor model was well fitting and consistent with the development of the original PrAS. Criterion-related validity was demonstrated by strong correlations with similar measures (PRAQ-R2, anxiety, and depression) and lower correlations with resilience scores. Predictive validity was shown by group comparisons for: planned versus unplanned pregnancy, trimester, and parity. Conclusions The PrAS-G provides a broader assessment of pregnancy-related anxiety than existing measures. Initial evaluation has demonstrated convergent, divergent, and predictive validity, excellent internal consistency, and good model fit indicating promising psychometric properties. The PrAS-G offers a comprehensive assessment of pregnancy-related anxiety which will enable tailored interventions aiming to improve birth experience and well-being of expectant mothers.